ANALISIS PRIORITAS PELAKSANAAN PERAWATAN DAN PEMELIHARAAN AKIBAT POTENSI KERUSAKAN BANGUNAN MINIMARKET ALFAMIDI DI KOTA MALANG MENGGUNAKAN METODE AHP - Adi Prabowo; Nemesius Bambang Revantoro; Cynthia Permata Dewi (Journal Innovation of Civil Engineering (JICE), 2023)
The decision on the priority for care and maintenance at Alfamidi Minimarket uses the AHP method to evaluate the decision for building care and maintenance to predict any potential damage to Alfamidi Minimarket. Thus, numerous complaints may be reduced, and building quality can be maintained to assure customer safety and comfort while shopping at Alfamidi Minimarket. The objectives of this research are as follows: (1) to determine the condition analysis of Alfamidi Minimarket in Malang, (2) to obtain a priority scale for implementing care and maintenance at Alfamidi Minimarket in Malang using the AHP method and Expert Choice V.11 Application modeling. This research applied a quantitative approach with a descriptive analysis technique; the sampling procedure was purposive sampling, and 13 Alfamidi Minimarkets in Malang served as the sample. The subjects of the research were Alfamidi and shop employees. The data collection method used a form about the building condition and a priority weighting questionnaire as supporting data. The Analytical Hierarchy Process (AHP) method can be utilized in making decisions since it systematically has multi-criteria properties to describe a problem. The analysis results show that: (1) The average condition of Alfamidi Minimarket in Malang based on the building condition index shows a good category with a percentage of 82.0669% with an average architectural component index (IKK) of 77.8%, a structural IKK of 97.75 %, Utilities IKK was 88.28%, and Environmental Management IKK was 63.0%. (2) According to the priority results, Alfamidi Dieng had the lowest building condition index at 78.99%, while Alfamidi Sigura-Gura had the highest at 85.82% Keywords: Priority; Care and Maintenance Building; AHP Method.